Natura Non Facit Saltus: The Adaptive Significance of Arginine Vasopressin in Human Affect, Cognition, and Behavior - Crespi, Bernard; Procyshyn, Tanya; Mokkonen, Mika (Frontiers in Behavioral Neuroscience, 2022)
Hormones coordinate internal bodily systems with cognition, affect, and behavior, and thereby influence aspects of social interactions including cooperation, competition, isolation, and loneliness. The adaptive significance and contextuality of oxytocin (OXT) and testosterone (T) have been well-studied, but a unified theory and evolutionary framework for understanding the adaptive functions of arginine vasopressin (AVP) remain undeveloped. We propose and evaluate the hypothesis that AVP mediates adaptive variation in the presence and strength of social and sociosexual salience, attention and behavior specifically in situations that involve combinations of cooperation with conflict or competition. This hypothesis can help to explain the ancestral, original functions of AVP-like peptides, and their continuity with the current roles of AVP, for humans, in male-male competition, male-male reciprocity, male-to-female pair bonding, female-female interactions, social integration, and social attention and anxiety. In this context, social isolation and loneliness may be mediated by reduced abilities or interests in navigation of social opportunities and situations, due in part to low AVP levels or reactivity, and in part to reductions in levels of OXT-mediated social reward.